Interpretação dos atos de fala : o papel da abdução - Castro Neto, José Carlos Camillo (2020)
This master’s thesis has as its goal to study the operation of an interpretation of speech acts. So, the main problem dealt with in here is: how works the interpretation of a speech act? Before starting the research, some choices were made which guided its enterprise. The first one is the acceptance of the theory of speech acts as an acceptable proposal for the study of natural languages. The second choice made was to accept that Intentionality has an important role in the production and interpretation of speech acts. From this perspective, the theory of speech acts according to the proposal of John Searle was analyzed and, according to it, interpretation consists in the correct application of conventional rules of the language in question. However, this proposal cannot explain cases like the one of metaphors, in which conventional rules are not enough for a succeeded interpretation. Therefore, the semiotics of Charles Peirce was also analyzed in order to, through comparation, understand what is in absence in Searle’s theory and realize if that which is lacking in Searle’s theory is necessary to explain like metaphors in which conventional rules are not enough for such explanation. It was found that abduction is the missing detail in the searlean theory of interpretation. Nevertheless, to define abduction is not an easy endeavor, but a definition that is harmonic with the pearcean semiotics and with empirical evidences is that abduction is a set of strategic rules. More specifically, the principle of coherence, the principle of economy, and the principle of non-contradiction. This study concluded that the interpretation of speech acts is the correct application of two kinds of rules: conventional rules of a particular language and strategic rules, which constitutes what is called abduction.